Adjacency preserving maps on upper triangular matrix algebras - Chooi, W (2003)
Let n be an integer, n greater than or equal to 3, and T-n the algebra of all real n x n upper triangular matrices. We describe the general form of maps on T-n that preserve the adjacency in both directions. We apply this result to characterize the semigroup of injective continuous maps on T-n preserving the adjacency in one direction only. (C) 2003 Elsevier Science Inc. All rights reserved.